Proteomic analysis reveals changes in the proteome of human THP-1 macrophages infected with Paracoccidioides brasiliensis - de Figueiredo, Ana Marina Barroso; Moraes, Dayane; Bailão, Alexandre Melo; Rocha, Olivia Basso; Silva, Lana Ohara Souza; Ribeiro-Dias, Fátima; Soares, Célia Maria de Almeida (Frontiers in Cellular and Infection Microbiology, 2023)
Paracoccidioides spp. is the etiologic agent of Paracoccidioidomycosis (PCM), a systemic disease with wide distribution in Latin America. Macrophages are very important cells during the response to infection by P. brasiliensis. In this study, we performed a proteomic analysis to evaluate the consequences of P. brasiliensis yeast cells on the human THP-1 macrophage proteome. We have identified 443 and 2247 upregulated or downregulated proteins, respectively, in macrophages co-cultured with yeast cells of P. brasiliensis in comparison to control macrophages unexposed to the fungus. Proteomic analysis revealed that interaction with P. brasiliensis caused metabolic changes in macrophages that drastically affected energy production pathways. In addition, these macrophages presented regulated many factors related to epigenetic modifications and gene transcription as well as a decrease of many proteins associated to the immune system activity. This is the first human macrophage proteome derived from interactions with P. brasiliensis, which contributes to elucidating the changes that occur during the host response to this fungus. Furthermore, it highlights proteins that may be targets for the development of new therapeutic approaches to PCM.